Redefining the Mode of HIV Transmission through Analysis of Risk Attribution among the Reported HIV Cases from 1993 to 2021 in Bhutan - Lekey Khandu; Ngawang Choida; Jurmi Drukpa; Dolley Tsehring; Sonam Wangdi (AIDS Research and Treatment)
Introduction. The detailed risk assessment of the diagnosed HIV cases in Bhutan is an opportunity to carry out the risk analysis to generate evidence of wherein, under what context, and in which population groups most new infections are occurring. The evidence collected will help to test the current assumption of Bhutan experiencing diffused and generalized HIV epidemic. Methods. This is a cross-sectional study using a quantitative method to assess the risk behavior of the diagnosed HIV cases from 1993 to 2019. The study also included secondary data analysis of those cases already captured by the routine case-based surveillance from 2020 to 2021. The data collection was done from 1 to 30 January 2022 in all the twenty districts of Bhutan. Descriptive statistical analysis was used to analyze the characteristics of the study population, and relationships were established using the Chi-square Test. We have sought ethics approval and obtained participants’ informed consent. Results. The risk attribution analysis showed that 81.94% of HIV infection among the reported HIV cases in Bhutan has occurred through high-risk heterosexuals and 8.88% through mother-to-child transmission, and parenteral transmission accounts for 1.58% and then 1.35% through homosexual. Of the 81.94% high-risk heterosexuals, 41.08% acquired through sex workers and clients of sex workers, 27.99% from HIV-infected persons, 12.64% from sex work, and 0.23% from injecting drug use. Conclusions. This study has shed some light on a gradual epidemic shift from the current perceived diffused and generalized to the concentrated epidemic among subpopulation groups like female sex workers and their clients.